A comparative approach to confirm antibiotic-resistant microbes in the cryosphere - Gattinger, Daniel; Pichler, Katrin; Weil, Tobias; Sattler, Birgit (Frontiers in Microbiology, 2023)
Antibiotic-resistant microbes pose one of the biggest challenges of the current century. While areas with proximity to human impact are closely studied, a lot is yet to learn about antimicrobial resistance in remote regions like the cryosphere. Nowadays, antibiotic (AB) resistance is considered a pollution that has reached the Earth’s most pristine areas. However, monitoring of resistant environmental bacteria therein faces several challenges that inhibit scientific progress in this field. Due to many cultivation-based antibiotic susceptibility tests being optimized for mesophilic pathogenic microorganisms, many researchers opt for expensive molecular biological approaches to detect antibiotic resistance in the cryosphere. However, some disadvantages of these methods prohibit effective comprehensive monitoring of resistant bacteria in pristine areas, hence we suggest established cultivation-based approaches when looking for antimicrobial resistance in the cryosphere. In this study, we compared two common antibiotic susceptibility tests and optimized them to meet the needs of psychrophilic microorganisms. The resulting cultures thereof originated from cryospheric habitats with differing anthropogenic impacts. The results show that these methods are applicable to detect antibiotic resistance in cryospheric habitats and could potentially increase the comparability between studies.